2015
DOI: 10.1016/j.jtherbio.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Isothermic and fixed intensity heat acclimation methods induce similar heat adaptation following short and long-term timescales

Abstract: Heat acclimation requires the interaction between hot environments and exercise to elicit thermoregulatory adaptations. Optimal synergism between these parameters is unknown. Common practise involves utilising a fixed workload model where exercise prescription is controlled and core temperature is uncontrolled, or an isothermic model where core temperature is controlled and work rate is manipulated to control core temperature. Following a baseline heat stress test; 24 males performed a between groups experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
104
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 80 publications
16
104
0
1
Order By: Relevance
“…During this study, T re rose linearly with time during HA, however, lower T repeak were evident in all groups across the four sessions, suggesting the magnitude of physiological strain was not sufficiently elevated compared to other studies (Patterson, et al, 2004;Garrett, et al, 2009Garrett, et al, , 2011Gibson et al, 2015). This may have led to reduced and partial adaptive responses, whereas, if controlled hyperthermia was administrated, greater adaptation may have been achieved (Fox, et al, 1973).…”
Section: 2mentioning
confidence: 54%
See 3 more Smart Citations
“…During this study, T re rose linearly with time during HA, however, lower T repeak were evident in all groups across the four sessions, suggesting the magnitude of physiological strain was not sufficiently elevated compared to other studies (Patterson, et al, 2004;Garrett, et al, 2009Garrett, et al, , 2011Gibson et al, 2015). This may have led to reduced and partial adaptive responses, whereas, if controlled hyperthermia was administrated, greater adaptation may have been achieved (Fox, et al, 1973).…”
Section: 2mentioning
confidence: 54%
“…However, despite total phenotypic adaptations occurring within 14 to 21 days during LTHA, ≤ 5 daily exposures during short term HA (STHA) facilitates practically significant thermoregulatory and cardiovascular (~75%) adaptations (Pandolf, 1998), over a more applicable duration for athletes and military personnel. Previous STHA studies (Cotter et al, 1997;Patterson et al, 2004;Sunderland et al, 2008;Garrett et al, 2009Garrett et al, , 2011Costa et al, 2014;Mee et al, 2015;Gibson et al, 2015) have reported physiological and athletic performance improvements within hot conditions. During training, prior to competition or in the lead up to military deployment, STHA may appear more feasible for inclusion in established schedules due to lesser disruption and costs, particularly when tapering and will avoid unnecessary reductions in the quality of training or heat-related illnesses.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, repeated 8 exposure to heat and exercise may be beneficial in some circumstances. Given suitable 9 preparation and safeguard exercise in the heat on repeated occasions may lead to 10 improved performance, a process termed acclimation (Gibson et al 2015). Berkshire) and Woodway (ELG2, GmbH) treadmills set at 1% incline (Jones and 5 Doust, 1996).…”
mentioning
confidence: 99%